Promoting Midwifery Students’ Speaking Ability Using Communicative Language Teaching - Arief Pamuji; Agus Wahyudi (International Journal of English and Applied Linguistics (IJEAL), 2022)
Speaking is the way to convey the information that must be acquired by students. Consequently, this study aimed to see whether Communicative Language Teaching could promote midwifery students’ speaking ability or not. In conducting this research, a quasi-experimental method was employed using a nonequivalent groups design. The sample taken was the second-semester student midwifery from STIK Bina Husada consisting of 38 students. To gather data, the oral test was employed. The speaking test was considered valid in terms of content validity and reliability. The reliability of the test was measured using inter-rater reliability. The results revealed that the t-obtained (5.42) was higher than the t-table (2.02) at the significant level of p<0.05. It can be concluded that Communicative Language Teaching could promote students speaking ability. Communicative Language Teaching could motivate students to be brave and self-confident in speaking performance and more active in using English as their spoken language in-class activities.